Some Properties of Subclasses of Multivalent Functions - Muhammet Kamali; Fatma Sağsöz (Abstract and Applied Analysis)
The authors introduce two new subclasses denoted by ℑ∗(Ω,𝜆,𝑝,𝛼) and ℑ∗𝜀(Ω,𝜆,𝑝,𝛼) of the class 𝐴(𝑝,𝑛) of 𝑝-valent analytic functions. They obtain coefficient inequality for the class ℑ∗(Ω,𝜆,𝑝,𝛼). They investigate various properties of classes ℑ∗(Ω,𝜆,𝑝,𝛼) and ℑ∗𝜀(Ω,𝜆,𝑝,𝛼). Furthermore, they derive partial sums associated with the class ℑ∗𝜀(Ω,𝜆,𝑝,𝛼).